Comparison of Zooplankton Abundance Vertically and Horizontally in The Waters of Boulevard II, Manado City - Utomo, Victoria O.S.E.; Rimper, Joice R.T.S.L; Bara, Robert A.; Mamuaja, Jane M.; Wagey, Billy T.; Sumilat, Deiske A. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
Zooplankton are microscopic organisms that play an important role in the marine food chain as primary consumers and as a food source for other organisms. Their presence and composition can serve as indicators of the health of aquatic ecosystems. This study was conducted in the waters of Boulevard II, Manado City, using a plankton net equipped with a cod end. Samples were collected vertically at a depth of 5 m and horizontally along a 10 m transect. Physico-chemical parameters such as temperature, salinity, and dissolved oxygen (DO) were measured in situ at each station using a Water Quality Monitor. Zooplankton identification was carried out at the Bio-Ecology Laboratory, Faculty of Fisheries and Marine Science, using a microscope and referring to Illustrations of the Marine Planktons of Japan (Yamaji, 1979) and WoRMS data. The results showed that the zooplankton found belonged to the class Copepoda, e.g. Nauplii, Acartia sp., Oithona sp., and Paracalanus sp.. The highest vertical abundance was recorded at station 1 with 11.51 Ind/L, while the lowest was at station 2 with 6.99 Ind/L. Horizontally, the highest abundance occurred at station 2 with 6.04 Ind/L and the lowest at station 1 with 3.21 Ind/L. These variations were influenced by temperature, salinity, and dissolved oxygen, which affect the distribution of zooplankton. Keywords : comparison, horizontal, vertical, zooplankton   Abstrak Zooplankton merupakan organisme mikroskopis yang berperan penting dalam rantai makanan laut sebagai konsumen primer dan sumber makanan bagi organisme lain. Kehadiran serta komposisi zooplankton dapat menjadi indikator kesehatan ekosistem perairan. Penelitian ini dilakukan di Perairan Boulevard II, Kota Manado, menggunakan plankton net yang dilengkapi cod end. Pengambilan sampel dilakukan secara vertikal pada kedalaman 5 m dan horizontal sepanjang 10 m. Parameter fisika-kimia seperti suhu, salinitas, dan oksigen terlarut (DO) diukur secara in situ menggunakan Water Quality Monitor di setiap stasiun. Identifikasi zooplankton dilakukan di Laboratorium Bio-Ekologi Fakultas Perikanan dan Ilmu Kelautan menggunakan mikroskop dengan acuan Illustrations of the Marine Planktons of Japan (Yamaji, 1979) dan data WoRMS. Hasil penelitian menunjukkan bahwa zooplankton yang ditemukan berasal dari kelas Copepoda, yaitu Nauplii, Acartia sp., Oithona sp., dan Paracalanus sp.. Kelimpahan vertikal tertinggi terdapat di stasiun 1 sebesar 11,51 Ind/L dan terendah di stasiun 2 sebesar 6,99 Ind/L. Secara horizontal, kelimpahan tertinggi terdapat di stasiun 2 sebesar 6,04 Ind/L dan terendah di stasiun 1 sebesar 3,21 Ind/L. Variasi kelimpahan ini dipengaruhi oleh suhu, salinitas, dan oksigen terlarut yang memengaruhi penyebaran zooplankton. Kata kunci: perbandingan, horizontal, vertikal, zooplankton